Implications of Schema Theory on Teaching EFL and ESL Reading comprehension: the Role of Pre-Reading Activities: The Case of ENSAM Meknes - Khartite, Brahim (International Journal of Linguistics and Translation Studies, 2021)
A great many research studies related to schema theory have made it unambiguously clear that the readers’ background knowledge is vitally crucial in reading comprehension. Used as an umbrella term, background knowledge subsumes a set of schemata and sub-schemata (including cultural content, linguistic formal as well as strategic) that readers use to get an accurate understanding of the content of any material they set out to read. However, one of the major problems underlying comprehension instruction at various proficiency levels in Morocco is that rarely do teachers take the role of background knowledge into account. It is not a common practice among Moroccan high school teachers when it comes to teaching reading to provide EFL readers with enough explicit information or prior instruction assistance to allow them easier comprehension of the reading material in the textbooks used. It is unfortunate that this is still the case at a time when it is increasingly becoming obvious that for foreign language learners, one of the basic implications of schema theory is that comprehension rests as much on the availability as well as the activation of readers’ relevant schemata. This paper highlights the need for prior instruction in the form of pre-reading activities that have earned some empirical support as practical teaching tools that facilitate ESL and EFL readers’ easy activation, construction and access of existing background knowledge and hence easier, better and above all more enjoyable and accurate comprehension.